Fenomenul sărăciei în rândul generaţiilor actuale de copii din România - Mihăilescu, Adina (Calitatea Vieții, 2017)
The objective of the study is to find out the extent of poverty and the satisfaction of human needs for the families with children in Romania. Some families are in difficult situations, even alarming, for example: the family with one adult and two or more children with a guaranteed minimum income and allowances for children; the family of two adults with two dependent children, that has a single net salary and allowances for those children. This families cannot cover the minimum decent living standard; the family in which one parent became unemployed, and so on, are some examples of population identified as needing support and social protection, and who are living in poverty or are in the risk of falling into poverty, getting far away from a decent life. The indicators which are used within the description and measuring of the intensity of poverty are the income and the consumption. Revenues from various types of consumers: person, family, household in relation with their consumption reflect the real purchasing power of goods and services on the market.